"INCREASING THE WELFARE OF THE "WORKING POOR" IN THE REPUBLIC OF MOLDOVA", CHALLENGES, CONSEQUENCES, SOLUTIONS - Dorin VACULOVSCHI (Eastern European Journal of Regional Studies)
The initiation of the transition to a market economy in the Republic of Moldova led to a drastic expansion of poverty. It should be emphasized that against the backdrop of hyperinflation at the beginning of the 90s and the privatization processes of the first years of the transition to the market economy, there was a strong decline in the real income of the population. In the category of people below the poverty line, could be included not only those from vulnerable groups, but also workers from the real and budgetary sector of the national economy, whose only source of income was their salary from employment. Thus, a fairly large economic social group was formed, namely the working poor which continues to exist to this day. On the other hand, the new economic realities led to the diversification of the population's forms of income, a phenomenon that was not characteristic of the socialist economy. This fact led to the spread of other forms of income and to the reduction of the role of the salary in the total income of the population. Against the backdrop of the economic transformations of the 1990s, there was a continuous decline in wages as the main source of income for the population. Consequently, the share of wages in the total disposable income of the population decreased to 37.8% by the year 2000. [13].The decrease in the role of the salary in the formation of the disposable income of the population in favor of other sources of income is a process of fire in the context the transition to the market economy. The population that managed to adapt to the new challenges of the time, successfully overcame the risk of poverty. Some managed to migrate; others started new businesses or engaged in other economic activities. Against this backdrop, social inequality among people intensifies. Unfortunately, the process of forming a class of prosperous business owners or "businesspeople" was only at the beginning, and they represented an extremely small number. Even to this day, a large expansion of the group of employers and businessmens in the Republic of Moldova is not noticeable. According to the Labor Force Survey, of the total employed population, only 3.9% were business owners (or employers) in 2023 [12], which indicates that there are problems in the chapter "entrepreneurial spirit", an indispensable condition for the development of the market economy. When the share of wages in the total income of the population becomes extremely small, a shift may occur in the function of reproducing the labor force from wages to other forms of income that are not directly linked to productive activity, such as non-labor-related activities. There is a strong decrease in occupational indicators, and a degradation of the human potential in the Republic of Moldova, thus undermining the functioning mechanism of the national economy for a longer perspective. In the situation where the salary no longer fulfills its basic economic and social functions, i.e. reproduction, motivation, stimulation of economic growth, the population no longer ties the fulfillment of their needs to work and employment in the labor market of the Republic of Moldova, opting instead for labor markets in other countries where wage conditions and working conditions are more favorable. The compromising of the role of wages in the economic life of the Republic of Moldova has led to the intensification of international labor migration and the degradation of the situation on the labor market, which seriously affects the prospect of economic recovery and sustainable economic development in the coming years.